2017
DOI: 10.1080/13645579.2017.1332848
|View full text |Cite
|
Sign up to set email alerts
|

What influences respondents to behave consistently when asked to consent to health record linkage on repeat occasions?

Abstract: This study constitutes the first longitudinal exploration of consent to link survey and administrative data. It examines variations in consent over time and explores the influence of the respondents' characteristics (both observed and latent) and the impact of the interviewers on consent co-operation. Respondent inclination to consent is modelled as a latent construct. Most respondents behave consistently over time. However, this consistency is not driven by a strong inclination to consent but rather by the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…At the same time, there has been a proliferation of data collected on individuals with information not frequently available in surveys. In response, efforts have been made to link these new sources of data to survey data to both address nonresponse and to add to the available data for analysis (e.g., Al Baghal, 2016; Eisnecker & Kroh, 2017; Mostafa & Wiggins, 2018; Sakshaug, Hülle, Schmucker, & Liebig, 2017; Sakshaug, Couper, Ofstedal, & Weir, 2012). To link these data, survey researchers have to ask permission from respondents, both to obtain information to locate records (e.g., Twitter handles) and for ethical reasons.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, there has been a proliferation of data collected on individuals with information not frequently available in surveys. In response, efforts have been made to link these new sources of data to survey data to both address nonresponse and to add to the available data for analysis (e.g., Al Baghal, 2016; Eisnecker & Kroh, 2017; Mostafa & Wiggins, 2018; Sakshaug, Hülle, Schmucker, & Liebig, 2017; Sakshaug, Couper, Ofstedal, & Weir, 2012). To link these data, survey researchers have to ask permission from respondents, both to obtain information to locate records (e.g., Twitter handles) and for ethical reasons.…”
Section: Contextmentioning
confidence: 99%
“…Other respondent characteristics are frequently (but not always) found to be related to consent. Several studies have found females less likely to consent (Knies, Burton, & Sala, 2012; Sala et al, 2012), as well as there being a number of findings that minorities are less likely to consent to linkage (Al Baghal, 2016; Kho, Duffett, Willison, & Brouwers, 2009; Knies & Burton, 2014; Knies et al, 2012; Mostafa & Wiggins, 2018).…”
Section: Contextmentioning
confidence: 99%
“…Regardless of interviewer characteristics associated with consent rate, the literature points to substantial interviewer variance in consent rates (Korbmacher & Schröder, 2013; Mostafa & Wiggins, 2017; Sakshaug et al, 2012). For instance, Korbmacher and Schröder (2013) observe interviewer intraclass correlation levels on the consent decision of over 40% even after controlling for respondent- and interviewer-level characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, even when cooperation is obtained, respondents may not consent to every individual biomeasure. The general issue of non-consent to health survey data collection has garnered much attention in the literature, including in this very journal (Al Baghal, 2016;Mostafa, 2016;Mostafa & Wiggins, 2018). Non-consent is particularly common for blood collection -one of the more invasive survey biomeasures (Jaszczak et al, 2009;S.L.…”
Section: Introductionmentioning
confidence: 99%